Performance evaluation for high speed vehicle in VANET - Alwan, Mohammed Hasan; Ramli, Khairun N. (Integrated Publishing Association, 2018)
Vehicular Ad hoc Networks (VANETs) is a high dynamic emerging technology for supporting wireless communication among vehicles. Communication via routing packets over the high-speed vehicles is a challenging task. Vehicles mobility speed can varies depending on the road specification. However in highways speed can be increased up to 120 – 200 Km/hr. moving in high speed can affect the efficiency of data delivery. In particular V2I traffic where moving car trying to deliver data to fixed space units which are designed to collected and process data from vehicles. In this paper, we investigated the consequences on increasing vehicle mobility speed in term of data delivery evaluation metrics including network throughput, delay and packet delivery ration. Results shows that in high speed mobility VANET, network throughput it decreased, and packet delivery ration is decreased as well.